Identifikasi Miskonsepsi Siswa Pada Materi Tumbuhan Dengan Two Tier Diagnostic Test - Hutami, Cahya Amalia; Kurniawati, Wahyu (Universitas Muhammadiyah Magelang, 2025)
Every subject given to students does not escape a concept, including learning Natural Sciences (Science). Concepts are a basic aspect of developing the knowledge learned by someone. Unfortunately, in reality, there are still many misconceptions in learning. The aim of this research is to identify students' misconceptions about plant material at SD N Krapyak Wetan. The research method used was quantitative description using diagnostic test instruments. Based on the diagnostic tests carried out, it is known that the percentage of students' misconceptions about plant material is quite high, especially in the sub-chapter on plants and photosynthesis with a percentage of 61%. Several factors cause misconceptions in students, namely 1) Teachers' lack of understanding about students' preconceptions before learning is carried out, 2) The use of learning methods that seem like that, less innovative, 3) The use of teaching materials must also be carefully considered because this is also the cause of misconceptions in students, 4) Then there is a lack of learning innovation such as simple experimental practices which are still very rarely carried out in schools.